SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN KETUA PAR GKI SION SANGGENG MENGGUNAKAN METODE WEIDTED PRODUT: Decision Support System for the Election of the Chairman of the Sanggeng Par Gki Sion Using the Weighted Product Method - Nadya Paulina; Lion Ferdinand Marini; Alex De Kweldju (Universitas Papua, 2023)
The selection of PAR chairpersons at the Sanggeng Zion CongregationalBible Christian Church is still relatively manual, for this reason this studyaims to create a decision-making system for selecting PAR chairpersons basedon existing criteria. This study uses the WEIGHTED PRODUCT method withstages, namely each criterion is ranked based on the level of importance. Thengiven a weight so that the normalized value can be calculated. In order toevaluate the expected alternatives, single attribute utilities are calculated sothat the resulting output is a decision support system in the form of a rankingwith the order of the greatest value. This application is designed using the PHPand MySQL programming languages. The results obtained from this studywere Sister Thersia Makabori becoming Chair of the PAR with the highestscore of 0.24 to be recommended as Chair of the PAR at GKI Sion SanggengManokwari based on the criteria that met the highest score.